Species composition of sea stars (Echinodermata: Asteroidea) in the Patagonian Argentinian deep sea, including seven new records: connectivity with sub-Antarctic and Antarctic fauna - Hurtado-García, Jennifer; Manjón-Cabeza-Cloute, María Eugenia (Springer, 2022)
The main target of this paper is to improve the knowledge of the species composition of sea stars in Patagonian Argentine deep sea reaching depths of 2062 m. In addition, these results offer us the opportunity to analyze the possible connections between Argentinian marine fauna and adjacent Antarctic areas that have become a topic of interest in the past few years. This work is based on Atlantic Projects’ surveys carried out on an atypical and especially vulnerable marine ecosystems (canyons created from craters collapse by gas leaks). These are profusely impacted by frequent fishing activities, being one of the most important and international fishing grounds, where 887 records (1878 specimens) of 41 species of asteroids were collected in 217 stations ranging from 219 to 2062 m in depth. Seven of those species are proposed as new records: (Diplasterias octoradiata (Studer 1885), Plutonaster bifrons (Wyville Thomson, 1873), Radiaster elegans Perrier, 1881, Anseropoda antarctica Fisher, 1940, Pillsburiaster calvus Mah, 2011, Paralophaster lorioli (Koehler, 1907), Pteraster flabellifer Mortensen 1933). After refining the database built from literature and open-access databases such as OBIS and AntBIF, the new Argentinian asteroids deep-water checklist contains 2198 records from 64 asteroids species including the 7 new records proposed. Most of these 64 species (89.06%) are present in Antarctic-adjacent waters, and after the study of their occurrences at traditional biogeographic entities, our results support the hypothesis that Argentinian waters (in the case of the class Asteroidea) should be considered part of the sub-Antarctic entity.
Keywords: Estrellas de mar; Asteroids; Asteroidea; Argentine; Antarctica